2003
DOI: 10.1172/jci200315830
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-C gene therapy augments postnatal lymphangiogenesis and ameliorates secondary lymphedema

Abstract: Although lymphedema is a common clinical condition, treatment for this disabling condition remains limited and largely ineffective. Recently, it has been reported that overexpression of VEGF-C correlates with increased lymphatic vessel growth (lymphangiogenesis). However, the effect of VEGF-C–induced lymphangiogenesis on lymphedema has yet to be demonstrated. Here we investigated the impact of local transfer of naked plasmid DNA encoding human VEGF-C (phVEGF-C) on two animal models of lymphedema: one in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 34 publications
5
86
2
4
Order By: Relevance
“…Importantly, both of the latter models are strongly TNF dependent. Conversely, application of VEGF-C or tumor-derived VEGF-C have been found to enhance lymphatic function and flow, respectively Szuba et al, 2002;Yoon et al, 2003;Hoshida et al, 2006;Tammela et al, 2007). The impaired lymphatic drainage might also explain the accumulation of CD11b + cells that we observed after blockade of VEGFR-3.…”
Section: Discussionmentioning
confidence: 69%
“…Importantly, both of the latter models are strongly TNF dependent. Conversely, application of VEGF-C or tumor-derived VEGF-C have been found to enhance lymphatic function and flow, respectively Szuba et al, 2002;Yoon et al, 2003;Hoshida et al, 2006;Tammela et al, 2007). The impaired lymphatic drainage might also explain the accumulation of CD11b + cells that we observed after blockade of VEGFR-3.…”
Section: Discussionmentioning
confidence: 69%
“…Administration of a VEGF-C-expressing adenovirus enhanced generation of functional lymphatic vessels in Chy mutant mice (Karkkainen et al 2001), and adenoviral delivery of VEGF-C in normal skin or at the edge of epigastric skin flaps in mice strongly induced lymphangiogenesis (Enholm et al 2001;Saaristo et al 2004). In addition, recombinant VEGF-C was shown to be sufficient to activate in vivo lymphangiogenesis and reversed the symptoms of lymphedema in rabbit ears (Szuba et al 2002); VEGF-C gene therapy stimulated postnatal lymphangiogenesis and thus ameliorated secondary lymphedema in animal models (Yoon et al 2003). More recently, using a newly established mouse model in which the axillary lymph nodes were removed to better recapitulate human breast cancer lymphadenectomy, Tammela et al (2007) have shown that collecting lymphatic vessels could be efficiently regenerated and connected to transplanted lymph node in the lymphedema area.…”
Section: Lymphedema Therapy-beyond Physical Compressionmentioning
confidence: 99%
“…As plaquetas se agregam em locais de comunicação entre a veia cardinal e sacos linfáticos e "sela" os vasos linfáticos da veia cardinal, separando os dois vasos (SCHULTE-MERKER; SABINE; PETROVA, 2011). As plaquetas são importantes para manter esses dois sistemas vasculares separados: a depleção de plaquetas ou defeito de agregação plaquetária leva à conexões linfovenosas anormais e à vasos linfáticos cheios de sangue (ICHISE et al, 2009;BERTOZZI et al, 2010;CARRAMOLINO et al, 2010;SUZUKI-INOUE et al, 2010;UHRIN et al, 2010 ROCKSON, 1998;YOON et al, 2003;CHEUNG et al, 2006;SAITO et al, 2006 ROCKSON, 1998;KARKKAINEN et al, 2001;YOON et al, 2003;SAARISTO et al, 2004;CHEUNG et al, 2006;SAARISTO et al, 2006;TAMMELA et al, 2007) (APRELIKOVA et al, 1992;GALLAND et al, 1992;JOUKOV et al, 1996;LEE et al, 1996). Apesar do VEGFR3 desempenhar um papel fundamental para o desenvolvimento celular endotelial vascular e linfático, sua expressão fica limitada ao endotélio linfático nos estágios finais de desenvolvimento (KAIPAINEN et al, 1995;KUKK et al, 1996;BAUMGARTNER et al, 1998 FERRELL et al, 1998;KARKKAINEN et al, 2000).…”
Section: Células Hematopoiéticas E Desenvolvimento Vascular Linfáticounclassified
“…Porém, com a realização do tratamento com VEGFC, pode-se observar um aumento significativo em ambas essas variáveis para a pele, indicando que o tratamento com VEGFC causou mudanças significativas na revascularização linfática nesta região (CHEUNG et al, 2006;PAN et al, 2006 (OASHI et al, 2012;KUWAHARA et al, 2013;OASHI et al, 2013). Outra possibilidade pode ser o fato da proximidade dessa região com o local de aplicação do VEGFC exógeno, uma vez que a aplicação foi realizada intraperitonealmente próxima à região da cicatriz cirúrgica (YOON et al, 2003).…”
Section: Marcação De Vegfc E Flt4 Porunclassified
See 1 more Smart Citation